Suppression of Trim32 Enhances Motor Function Repair after Traumatic Brain Injury Associated with Antiapoptosis. Issue 7 (July 2017) - Zhang, Zi-Bin; Xiong, Liu-Lin; Lu, Bin-Tuan; Zhang, Hui-Xiang; Zhang, Piao; Wang, Ting-Hua
To investigate the role of Trim32 in traumatic brain injury (TBI), adult male Sprague Dawley (SD) rats and mice were randomly divided into sham (n = 6) and TBI groups ( n = 24), respectively. Then, mice were assigned into Trim32 knockout mice (Trim32-KO [+/−]) and wild-type (WT) littermates. The TBI model used was the Feeney free-falling model, and neurological function was evaluated after TBI using a neurological severity score (NSS). Reverse transcription polymerase chain reaction (RT-PCR), Western blot, and immunohistochemistry were used to investigate the expression of Trim32 in the damaged cortex. Cell apoptosis in the cortex was detected by terminal-deoxynucleoitidyl transferase-mediated dUTP nick end labeling (TUNEL) staining. Moreover, Trim32-KO (+/−) mice were used to determine the effect of Trim in neurological repair after TBI. Results showed the NSS scores in TBI rats were significantly increased from day 1 to day 11 postoperation, compared with the sham group. Trim32 messenger RNA (mRNA) expression in the cortex was significantly increased at 7 d after TBI, while the level of Tnr and cytochrome c oxidase polypeptide 5A mRNA didn't exhibit significant changes. In addition, Western blot was used to detect the level of Trim32 protein in the cortex. Trim32 expression was significantly increased at 7 d after TBI, and immunoreactive Trim32-positive cells were mainly neurons. Moreover, Trim32-KO (+/−) mice with TBI had lower NSS scores than those in the WT group from day 1 to day 11 postoperation. Meanwhile, Trim32-KO (+/−) mice had a decreased number of TUNEL-positive cells compared with the control group at 3 d postoperation. Protein 73 (p73) decreased at 7 d postoperation in Trim32-KO (+/−) mice with TBI, when compared with WT mice with TBI. Our study is the first to confirm that suppression of Trim32 promotes the recovery of neurological function after TBI and to demonstrate that the underlying mechanism is associated with antiapoptosis, which may be associated with p73.